- BA = 0
- B = 0
- B(1-A) = 1
- C + B + A = 0
- (1-B)(1-A) = 1
- (1-C)(2 - B - A) = 1
- C = 1
- (2 - C + A)(2 - C + B) = 1
- CB = 0
- CBA = 0 (needs 2 constraints !!)
- D + C + B + A = 0
- D + C + B = 0
- D + C + BA = 1
- D + C = 0
- D + CB + CA = 0
- D + CB = 0
- D + CBA = 0
- D = 0
- D(C + B + A) = 0
- D(C + B) = 0
- DC + DBA = 0 (needs 2 constraints !!)
- CD = 0
- DC(B + A) = 0 (needs 2 constraints !!)
- DCB = 0 (needs 2 constraints !!)
- DCBA = 0 (needs 3 constraints !!)
if p then a else b <=> (1-p)b + pa
if p then 1 else b <=> (1-p)b + p
if p then 0 else b <=> (1-p)b
if p then a else 1 <=> 1 - p + pa
if p then a else 0 <=> pa